What Is Anti-Government Extremism? - Jackson, Sam (Perspectives on terrorism, 2022)
Researchers studying extremism commonly use ideological categories to describe actors, actions, and ideologies. One such category is anti-government extremism. This article attempts to define and clarify this concept. After providing a basic definition, the analysis distinguishes ideological anti-government extremism from issue-driven anti-government extremism. The discussion examines whether this category should be seen as a subcategory of other categories (namely, right-wing extremism), as well as the relevance of this category when the government that extremists oppose changes. Several challenges to developing a universally applicable definition of anti-government extremism are identified, and it must be recognized that such a definition might not be useful for research focused on different extremist actors, actions, and ideologies in different political contexts. Finally, the discussion acknowledges the limits of using the definition developed through this article for (post-)positivistic research that would treat anti-government extremism as a variable to be measured across different cases.